2004
DOI: 10.1111/j.1365-2141.2004.05039.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of apoptosis induction in acute myeloid leukaemia‐relevance of karyotype and clinical treatment response

Abstract: Summary Deficiencies or structural defects of the apoptotic machinery have been postulated as a potential mechanism for a broad resistance of acute myeloid leukaemia (AML) blasts towards cytotoxic therapy comprising chemotherapeutic agents with diverse pharmacodynamic principles but also cell‐mediated cytotoxicity of the graft‐versus‐leukaemia effect, for example, in the setting of allogeneic transplantation. This hypothesis was systematically tested by functionally analysing the early, intermediate and late e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Antileukemic drugs like cytarabine in combination with daunorubicine and 6-thioguanine (TAD), or with mitoxantrone (HAM) cause DNA damage or inhibit DNA synthesis and, thus, kill tumor cells mainly by apoptosis [ 30 ]. The activation of caspases-3 and caspases-8 was already detected 12–24 hours after the application of the chemotherapeutic drugs [ 31 , 32 ]. Also morphologically, increasing numbers of apoptotic cells were observed after application of the cytotoxic therapy; for example mitoxantrone induced early apoptosis and showed a high rate of cell death of blast cells during the initial 24 hours [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antileukemic drugs like cytarabine in combination with daunorubicine and 6-thioguanine (TAD), or with mitoxantrone (HAM) cause DNA damage or inhibit DNA synthesis and, thus, kill tumor cells mainly by apoptosis [ 30 ]. The activation of caspases-3 and caspases-8 was already detected 12–24 hours after the application of the chemotherapeutic drugs [ 31 , 32 ]. Also morphologically, increasing numbers of apoptotic cells were observed after application of the cytotoxic therapy; for example mitoxantrone induced early apoptosis and showed a high rate of cell death of blast cells during the initial 24 hours [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also morphologically, increasing numbers of apoptotic cells were observed after application of the cytotoxic therapy; for example mitoxantrone induced early apoptosis and showed a high rate of cell death of blast cells during the initial 24 hours [ 14 ]. Another study reported cytarabine to induce cytotoxicity and to reduce the viability of bone marrow blasts by two thirds 24 hours and almost completely 96 hours after application of the drug [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 3 activation is not required for necrosis, and occurs very late or not at all in autophagy; it might therefore differentiate between these modes of cell death (Braess et al, 2004;Levine and Yuan, 2005). An intriguing feature of GAPDH is its intranuclear accumulation in response to nongenotoxic and genotoxic stimuli.…”
Section: Table 1 Molecular Dynamics Parameters Of Egfp and Egfp-gapdhmentioning
confidence: 99%
“…Each case was classified according to the FrenchAmerican-British (FAB) system (23). Cytogenetic abnormalities were classified as follows (24,25): favorable, inv (16) and t (8,21); unfavorable, abnormalities of chromosomes 5 and/or 7 and abnormalities involving 11q23 and complex abnormalities; intermediate, all other abnormalities. The hematological characteristics are summarized in Table 1 …”
Section: Patients and Treatment-study Designmentioning
confidence: 99%
“…The mechanisms of resistance are complex (1,(8)(9)(10)(11)(12) and do not clearly come from a dysfunctional apoptotic apparatus per se, but rather from a regulation impeding otherwise functional apoptotic machinery. These adaptive phenomena could impair the ability to achieve a durable complete remission (CR) with chemotherapy, leading to a relapse following CR, indicating that a part of the initial leukemic cells was withdrawn from the chemotherapy-induced cell death.…”
mentioning
confidence: 99%